Orientational preferences of neighboring helices can drive ER insertion of a marginally hydrophobic transmembrane helix - Öjemalm, Karin (2012)
α-helical integral membrane proteins critically depend on the correct insertion of their transmembrane α-helices into the lipid bilayer for proper folding, yet a surprisingly large fraction of the transmembrane α-helices in multispanning integral membrane proteins are not sufficiently hydrophobic to insert into the target membrane by themselves. How can such marginally hydrophobic segments nevertheless form transmembrane helices in the folded structure? Here, we show that a transmembrane helix with a strong orientational preference (N(cyt)-C(lum) or N(lum)-C(cyt)) can both increase and decrease the hydrophobicity threshold for membrane insertion of a neighboring, marginally hydrophobic helix. This effect helps explain the ‘missing hydrophobicity’ in polytopic membrane proteins.